Constraints as faced by the cauliflower growers in use of recommended cauliflower production technology - Ghaswa, Ramdhan; Sharma, N.K.; Kumari, Sunita; Bana, S.K. (Annals of Agricultural Research, 2016)
Cauliflower (Brassica oleracea var. botrytis) is one the most important as well as popular wintervegetable crops, which is grown through out the country. Vegetables play an important role inthe maintenance of human health. These make diet nutritive and balanced. A balanced diet requiresa proper quota of fresh vegetables. About 300 gm of vegetables are needed (90 gm root vegetables,120 gm green vegetables and 90 gm other vegetables). But, about 220.8 gm vegetables per dayper capita are available (Indian Agriculture, 2011). The present study was conducted in Jaipurdistrict of Rajasthan which was selected purposely. The Jaipur district consists of 13 panchayatsamities, Out of which two panchayat samities namely Bassi and Amber were selected on thebasis of the highest area and production. In all 12 villages were selected from the selected grampanchayats by using simple random sampling technique and a sample of 84 cauliflower growerswas selected from these villages by using proportionate random sampling technique. The ''financialconstraints'' and "marketing constraints" were most perceived by the cauliflower growers followedby "technical constraints". Whereas the "input constraints" were perceived least by the cauliflowergrowers.